Sarcasm Across Time and Space: Patterns of Usage by Age, Gender, and Region in the United States. Issue 1 (2nd January 2023) - Johnson, Alexander A.; Kreuz, Roger J.
ABSTRACT: Past research has highlighted some differences in how sarcasm is interpreted by different groups of individuals as well as biases in individuals' expectations regarding who is more likely to use it (e.g., occupation, gender). However, examinations of patterns of sarcasm production have been much less frequent. The current research extends past work highlighting the relationship between sarcasm production and demographic as well as geographic factors by extending this research to an online sample. Patterns of sarcasm production by age, gender, and geographic region within the United States were explored using three measures. Results revealed that older individuals and females showed decreased sarcasm use and were more likely to define sarcasm as negative, while geographic regions showed variation only in self-reported use. These results highlight some of the many factors associated with sarcasm use and further demonstrate the complexity of this contentious linguistic act.